Acanthagrion hartei sp. nov. from Ecuador (Zygoptera: Coenagrionidae) - Muzon, Javier (2005)
The new sp. is described and illustrated. Holotype: Ecuador, Morona, Santiago prov., Bomboiza, 20-IX-1990, deposited in USNM, Washington. It is assigned to the apicale-group, and differs from the other spp. of that group by characters of the terminalia and genital ligula.